Struktur Komunitas Parasitoid yang Berasosiasi dengan Liriomyza sativae (Blanchard) (Diptera:Agromyzidae) pada Berbagai Tanaman Inang di Dataran Rendah - HERLIANADEWI, NI MADE SERLI; SUPARTHA, I WAYAN; SUNARI, A. A. A. AGUNG SRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT Community Structure of Parasitoid Associated with Liriomyza sativae (Blanchard) (Diptera: Agromyzidae) on Several Host Plants in Lowlands The research purposed to find out the community structure of parasitoid that associating with Liriomyza sativae on several host plants conducted in the lowland area from October 2012 to January 2013. Leaf sampling was carried out at the center of vegetable and some horticultural crops in the lowland purposively. The number of leaf sample were taken about 20-30 infected-leaf of larvae of Liriomyza. Observation and identification of parasitoids were conducted in Laboratory of Integrated Plant Pest and Disease, Faculty of Agriculture, University of Udayana. The results showed that there are seven species of parasitoids associated with L. sativae in the lowlands. Parasitoid diversity was highest in long beans and cucumber.  Among the seven parasitoid, Opius sp., N. formosa and H. varicornis is more dominant  parasitoid and have a higher abundance than other parasitoids. Opius sp. have adapted to L. sativae associated with various types of host plants in the lowlands. Opius sp. also has the highest rate of parasitization on L. sativae on caisin (33.33%), followed by N. formosa on tomato (16, 09%) and H. varicornis on caisin (27, 27%). Keywords: The community  structure of parasitoid, Liriomyza sativae, and Host Plant.
Keywords: the community structure of parasitoid; Liriomyza sativae; host plant